Rapid mashup development tools : first International Rapid Mashup Challenge, RMC 2015, Rotterdam, the Netherlands, June 23, 2015, Revised selected papers /: first International Rapid Mashup Challenge, RMC 2015, Rotterdam, the Netherlands, June 23, 2015, Revised selected papers. (2016) - Unknown
No abstract available